2007
DOI: 10.1051/0004-6361:20078130
|View full text |Cite
|
Sign up to set email alerts
|

The surface brightness profile of the remote cluster NGC 2419

Abstract: Context. It is well known that the bright and remote Galactic globular cluster NGC 2419 has a very peculiar structure. In particular its half-light radius is significantly larger than that of ordinary globular clusters of similar luminosity, being as large as that of the brightest nuclei of dwarf elliptical galaxies. Aims. In this context it is particularly worthwhile checking the reliability of the existing surface brightness profiles for this cluster and the available estimates of its structural parameters. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2

Year Published

2010
2010
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 24 publications
6
52
2
Order By: Relevance
“…NGC 2419 resides at 90 kpc from the center of our Galaxy, has a half-mass and tidal radius of 20 pc and 230 pc, respectively, and a V −band luminosity of 5 × 10 5 L ⊙ (Harris 1996), which implies a total stellar mass of ≈ 10 6 M ⊙ . Bellazzini (2007) recently measured the stellar surface density of NGC 2419 to 200 pc. The core and half-mass relaxation times of this GC are 9 and 35 Gyr, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…NGC 2419 resides at 90 kpc from the center of our Galaxy, has a half-mass and tidal radius of 20 pc and 230 pc, respectively, and a V −band luminosity of 5 × 10 5 L ⊙ (Harris 1996), which implies a total stellar mass of ≈ 10 6 M ⊙ . Bellazzini (2007) recently measured the stellar surface density of NGC 2419 to 200 pc. The core and half-mass relaxation times of this GC are 9 and 35 Gyr, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of its surface brightness profile revealed some evidence for extratidal stars (Bellazzini 2007) and references therein). In Fig.…”
Section: Ngc 2419mentioning
confidence: 95%
“…Equations (5) and (6) have been derived by us from secondary standard stars in NGC 2419 (Bellazzini 2007). We interpolated the Schlegel et al (1998) reddening maps to obtain an estimate of E(B − V) for each source included in our final f1 and f2 catalogues.…”
Section: Astrometry Photometric Calibration and Reddeningmentioning
confidence: 99%